Late implant sepsis after fracture surgery in HIV positive patients. Issue 4 (April 2015) - Graham, Simon Matthew; Bates, Jes; Mkandawire, Nyengo; Harrison, William J.
Abstract: A prospective cohort study was undertaken to assess the incidence of late-implant sepsis after internal fixation in HIV-positive patients. A total of 91 HIV-positive patients (67 males and 24 females) who underwent 103 procedures (111 implants) were followed up for a mean period of 27 months (range 12–66 months). No occurrences of late implant sepsis were found in 100 implants (94 procedures) in 82 patients at 27 months' follow-up (range 12–66 months). Nine patients (9 procedures, 9 implants) developed early infections within 6 weeks and were treated with antibiotics (6 patients), amputation (1 patient) or removal of metal work (2 patients). There was no evidence of subsequent late implant sepsis in any of these patients, at a mean follow-up of 25 months (range 12–52 months). This study demonstrates that it is safe to perform internal fixation in HIV-positive patients, with no observed increase risk of late implant sepsis. There is no indication to remove implants after fracture union, other than for the general clinical indications that may lead to removal of metal work in any patient.